Inaugurating Rationalization: Three Field Studies Find Increased Rationalization When Anticipated Realities Become Current - Laurin, Kristin (Psychological Science, 2018)
People will often rationalize the status quo, reconstruing it in an exaggeratedly positive light. They will even rationalize the status quo they anticipate, emphasizing the upsides and minimizing the downsides of sociopolitical realities they expect to take effect. Drawing on recent findings on the psychological triggers of rationalization, I present results from three field studies, one of which was preregistered, testing the hypothesis that an anticipated reality becoming current triggers an observable boost in people’s rationalizations. San Franciscans rationalized a ban on plastic water bottles, Ontarians rationalized a targeted smoking ban, and Americans rationalized the presidency of Donald Trump, more in the days immediately after these realities became current compared with the days immediately before. Additional findings show evidence for a mechanism underlying these behaviors and rule out alternative accounts. These findings carry implications for scholarship on rationalization, for understanding protest behavior, and for policymakers.